2008
DOI: 10.1590/s0004-282x2008000300028
|View full text |Cite
|
Sign up to set email alerts
|

Transient central diabetes insipidus followed by pituitary apoplexy treated in a conservative way

Abstract: apoplexia hipofisária com TraTamenTo conservador seguido por diabeTes insipidus cenTral TransiTório 2,3 . These findings are often accompanied by various degrees of hypopituitarism, even without surgical management of the apoplexy. Even though, posterior pituitary function is nearly always preserved, a few cases of diabetes insipidus have been described 5,6 . Diabetes insipidus occurs transiently in about 4% of patients with apoplexy and persistently in only 2 % of these patients [5][6][7] . We report a patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In our study, we observed a frequency of 54% at admission that progressed to 60% at the last evaluation. Similarly, other studies showed that improvement in pituitary function after PA, independent of treatment should not be expected (6,37,42,46). One limitation of our study was that we could not precisely estimate the frequency of hypocortisolism in our patients because many patients were admitted to other centers before being transferred to ours and were already using high doses of dexamethasone/hydrocortisone or oral corticosteroids at admission in our center.…”
Section: Discussionmentioning
confidence: 81%
“…In our study, we observed a frequency of 54% at admission that progressed to 60% at the last evaluation. Similarly, other studies showed that improvement in pituitary function after PA, independent of treatment should not be expected (6,37,42,46). One limitation of our study was that we could not precisely estimate the frequency of hypocortisolism in our patients because many patients were admitted to other centers before being transferred to ours and were already using high doses of dexamethasone/hydrocortisone or oral corticosteroids at admission in our center.…”
Section: Discussionmentioning
confidence: 81%
“…Central diabetes insipidus is a rare complication of pituitary apoplexy, presenting in, it is estimated, less than 5% of cases, and is usually transient. 8 In some cases, it emerges after steroid replacement or postoperatively from pituitary resection. 3,7,9 The hypothalamus produces antidiuretic hormone, which migrates to the posterior pituitary gland with several sites above the gland involved in secretion of antidiuretic hormone.…”
Section: Hypopituitarism After Apoplexymentioning
confidence: 99%
“…Pituitary apoplexy more often involves only the anterior pituitary gland; the posterior gland or pituitary stalk may be involved if substantial mass effect or interruption in blood supply is present. 8 Glucocorticoid replacement may precipitate diabetes insipidus in the setting of adrenal insufficiency (Figure 4). Low cortisol levels will stimulate the release of antidiuretic hormone, increasing water reabsorption in the kidney, which can be inhibited by exogenous steroids, thereby rapidly manifesting diabetes insipidus; 10 this was likely the situation in this patient's course.…”
Section: Hypopituitarism After Apoplexymentioning
confidence: 99%